Adolescents and young adults’ concerns under stress, the COVID-19 pandemic: a Portuguese cross-sectional study - Silva, Carlos Franclim; Beirão, Daniel; Sá, Luísa; Santos, Paulo (Frontiers in Psychology, 2023)
Adolescents and young adults are a critical target regarding reducing health-risk behaviors' adoption, particularly in a stressful context such as the COVID-19 pandemic.Surveying their perceptions and behavioral changes may lead to a revised health promotion approach. This study aims to describe adolescents' and young adults' early reactions to a stressful event, the COVID-19 pandemic, characterizing their social determinants and preferences, such as sources of information, experienced symptoms, habits, and main concerns regarding themselves, their relatives, and the community.We intended to explore the association of their concerns and significant determinants such as age, gender, education, source of information, feelings of fear, prospecting the implications of communication, and individual and social determinants in managing stressful events. We conducted a cross-sectional, population-based, self-report survey of 3,898 individuals aged between 16 and 24 years from Portugal. The main concerns about COVID-19 were the possibility of transmitting to someone and permanent social changes. Our findings present significant differences according to gender, education, age, and expressing fear. The pandemic deteriorated baseline community inequalities.Young people appreciate official information and are available to contribute to society's safety. However, valuing official information is associated with deeper expressed concerns. Therefore, official information should include strategies to reach young people, promote healthier choices, and avoid distress and disinformation.